Brand Equity and Brand Loyalty: New Perspective - Abd M. Alkhawaldeh; Salniza Md. Salleh; Fairol Bin Halim (International Review of Management and Marketing, 2016)
Several studies have examined the antecedents of brand loyalty, whereas little research mentioned in political marketing context. This research empirically aims to investigate the relationship between multi dimensions of brand equity and loyalty to party brand among Jordanian voters in order to address the mixed results in earlier researches and to close this gap in literature of marketing. The research applies PLS-SEM techniques to a sample of 208 voters to test hypothesized relationships. Interestingly, the findings show that there is a positive support for two of hypotheses, meanwhile the others rejected.